Penggunaan Media Gambar dalam Meningkatkan Hasil Belajar pada Pembelajaran IPA di SDK Ende 3 - Alfonita Timu; Yuliani Sepe Wangge; Finsensius Mbabho (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This research aims to determine how the use of image media to improve learning outcomes on IPA learning in the SDK Ende 3. This research is class action research (CAR). The research subject is grade IV students. Data collection techniques are conducted through observation, test, and documentation. The results showed that student learning results were improved. On the pre test, the average class value was 64.57 and the classification was 34.28% and the average grade rate was increased to 89,42 with the classical dictancy of 100% on the I cycle. Based on the research results can be concluded that the use of image media can improve learning outcomes on natural science learning in the SDK Ende 3.